Community beliefs and practices about diabetes and their implications for the prevention and management of diabetes in Southeast Ghana - Stanley Kofi Alor; Irene Akwo Kretchy; Franklin N. Glozah; Philip Baba Adongo (BMC, 2024)
Abstract Background Diabetes is a major public health issue, and over half a billion people are estimated to be living with diabetes, with 6.7 million deaths reported in 2021. The global diabetes burden has been recognised and included in the United Nations Sustainable Development Goals to achieve a zero increase in diabetes cases and reduce one-third of premature diabetes deaths by 2030. However, local beliefs about the causes of diabetes have affected its prevention and management. This study examined community beliefs and practices about diabetes and how they affect the prevention and management of diabetes in the community. Methods This study was carried out in the Ho Municipality of the Volta Region of Ghana. We conducted 33 in-depth interviews with 18 patients with diabetes, 5 carers (caretakers of patients with diabetes), 3 traditional healers, 2 religious leaders, 3 community elders, and 2 assembly members who were purposefully selected from urban and rural areas across the municipality. The interviews were recorded digitally and transcribed verbatim. Thematic analysis was applied to analyse the data using QRS NVivo 20. Results Diabetes was described locally as sukli dɔ (sugar disease), which affects humans. Diabetes is believed to be caused by spiritual forces (juju, bewitchment, and punishment from gods) and physical factors (unhealthy diet, physical inactivity, eating fruits and vegetables sprayed with pesticides and insecticides, sugary and starchy foods, smoking, and abuse of alcohol). In terms of the management of diabetes, participants said traditional remedies are performed for spiritual interpretation, deliverance, fortification, and cleansing before biomedical and physical remedies are sought. Diabetes was likened to HIV/AIDS, and the sufferers were described as bringing the condition upon themselves as a result of their bad deeds. They were stigmatised, coupled with delays at the hospital, and poverty has also affected the prevention and management of diabetes. Conclusion The local belief that diabetes is caused by spiritual forces, likened to HIV/AIDS, delays at hospitals, and poverty, has affected the prevention and management of diabetes. Incorporating local beliefs and practices into the intervention design using culturally sensitive health education programmes and improving social determinants of health may help improve the prevention and management of diabetes in communities.